2022
DOI: 10.3847/1538-4357/ac6171
|View full text |Cite
|
Sign up to set email alerts
|

The Lick AGN Monitoring Project 2016: Dynamical Modeling of Velocity-resolved Hβ Lags in Luminous Seyfert Galaxies

Abstract: We have modeled the velocity-resolved reverberation response of the Hβ broad emission line in nine Seyfert 1 galaxies from the Lick Active Galactic Nucleus (AGN) Monitoring Project 2016 sample, drawing inferences on the geometry and structure of the low-ionization broad-line region (BLR) and the mass of the central supermassive black hole. Overall, we find that the Hβ BLR is generally a thick disk viewed at low to moderate inclination angles. We combine our sample with prior studies and investigate line-profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Comparison of modeling constraints with interferometry from GRAVITY shows good agreement in the black hole mass as well as the structural parameters of the BLR (NGC 3783, Gravity Collaboration 2021; Bentz et al 2021). Constraints on the BLR kinematics are consistent with those found from velocity-resolved reverberation mapping (RM) and the maximum entropy method (e.g., Villafaña et al 2022a), and inclination angles are consistent in the few cases in which independent measurements are available (Grier et al 2017;this work). Tests of simulated data also show reassuring results, in that the key properties of the BLR and the black hole mass are robustly recovered even when the input model is significantly different than what is assumed in CARAMEL (Mangham et al 2019).…”
Section: Model Limitationsmentioning
confidence: 54%
See 2 more Smart Citations
“…Comparison of modeling constraints with interferometry from GRAVITY shows good agreement in the black hole mass as well as the structural parameters of the BLR (NGC 3783, Gravity Collaboration 2021; Bentz et al 2021). Constraints on the BLR kinematics are consistent with those found from velocity-resolved reverberation mapping (RM) and the maximum entropy method (e.g., Villafaña et al 2022a), and inclination angles are consistent in the few cases in which independent measurements are available (Grier et al 2017;this work). Tests of simulated data also show reassuring results, in that the key properties of the BLR and the black hole mass are robustly recovered even when the input model is significantly different than what is assumed in CARAMEL (Mangham et al 2019).…”
Section: Model Limitationsmentioning
confidence: 54%
“…Previous studies that model velocity-resolved reverberation mapping data have consistently found a preference for BLR geometries that resemble a moderately inclined thick disk (Brewer et al 2011;Pancoast et al 2014b;Grier et al 2017;Williams et al 2018;Bentz et al 2021;Villafaña et al 2022a).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a growing number of cases, this has been modeled (e.g. Pancoast et al 2014b;Grier et al 2017;Williams et al 2018Williams et al , 2020Bentz et al 2021;Villafaña et al 2022, see more discussion below) but in general, an average value of f has been used.…”
Section: Introductionmentioning
confidence: 99%
“…Pancoast et al 2014b;Grier et al 2017;Williams et al 2018). This modeling is intensive, and requires densely sampled light curves, so it has only been done for 27 objects so far (Villafaña et al 2022). More comparisons are needed.…”
Section: Introductionmentioning
confidence: 99%